2017
DOI: 10.1177/0194599817698435
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Image‐Guided Cochlear Implant Programming at a Distant Site

Abstract: Our objective was to prospectively evaluate implementation of a new cochlear implant (CI) mapping technique, image-guided cochlear implant programming (IGCIP), at a site distant to the site of development. IGCIP consists of identifying the geometric relationship between CI electrodes and the modiolus and deactivating electrodes which interfere with neighboring electrodes. IGCIP maps for 17 ears of 15 adult CI patients were developed at a central image-processing center, Vanderbilt, and implemented at a distant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Applications of VE were classified into 5 subdomains: patient‐physician interaction (Supplemental Table 1a and 1b, available online), physician‐physician interaction (Supplemental Tables S2a and S2b), patient engagement tools (Supplemental Tables S3a and S3b), tele‐screening (Supplemental Tables S4a and S4b), and tele‐rehabilitation (Supplemental Table S5a and S5b). Most studies focused on feasibility 6–75 or investigated concordance rates…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Applications of VE were classified into 5 subdomains: patient‐physician interaction (Supplemental Table 1a and 1b, available online), physician‐physician interaction (Supplemental Tables S2a and S2b), patient engagement tools (Supplemental Tables S3a and S3b), tele‐screening (Supplemental Tables S4a and S4b), and tele‐rehabilitation (Supplemental Table S5a and S5b). Most studies focused on feasibility 6–75 or investigated concordance rates…”
Section: Resultsmentioning
confidence: 99%
“…Tele-consultation has been utilized among providers within 36 - 40 , 130 and beyond 35 , 127 - 129 the confines of the country. It is also useful in connecting ENT providers with those from different specialties in emergency situations or when a complex case is encountered requiring multidisciplinary care, 4 , 41 , 131 underscoring its potential in the field of otorhinolaryngology.…”
Section: Discussionmentioning
confidence: 99%
“…This limited the data available for meta-analysis to studies originating out of or associated with one research group (28–32). In addition, only summary measures could be analyzed because source data from several studies were lost or unavailable (31–34). The lack of a formal control group and randomization in the current studies also increases the risk of selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Labadie et al (31) found that, in 26 prelingually deafened patients (29 implants), only the 0.05-cycle/octave component of the SMD test improved, but a similar percentage of patients chose to keep their IGCIP map for long-term use (Table 1). McRackan et al (32) implemented the technology at a distant site on 15 postlingually deafened patients (17 implants) and found no significant improvement across any audiological assessment and a lower percentage of patients electing to keep the IGCIP map for long-term use (Table 1) Five of these studies shared similar experimental design, postadjustment follow-up time, and components of audiological assessments amenable to meta-analysis (28)(29)(30)(31)(32). All speech perception performance raw scores increased with use of the IGCIP map, but with a small magnitude of overall effect: CNC words, 0.15 (−0.12 to 0.42); AzBio quiet, 0.09 (−0.05 to 0.22); AzBio +10 dB signal-noise ratio, 0.14 (−0.01 to 0.30); and BKB-SIN, −0.11 (−0.35 to 0.12).…”
Section: Igcip For Channel Interactionsmentioning
confidence: 99%
“…Prior uses of telemedicine have used the technology to perform remote mapping and programming [15][16][17][18][19] , post-implantation testing 20,21 , remote intraoperative monitoring 22 , and remote clinical care of their cochlear implants 23 . This study is the first of its kind attempting to administer cochlear implant evaluations using telemedicine technology.…”
Section: Discussionmentioning
confidence: 99%